-3m+6=12

Simple and best practice solution for -3m+6=12 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -3m+6=12 equation:


Simplifying
-3m + 6 = 12

Reorder the terms:
6 + -3m = 12

Solving
6 + -3m = 12

Solving for variable 'm'.

Move all terms containing m to the left, all other terms to the right.

Add '-6' to each side of the equation.
6 + -6 + -3m = 12 + -6

Combine like terms: 6 + -6 = 0
0 + -3m = 12 + -6
-3m = 12 + -6

Combine like terms: 12 + -6 = 6
-3m = 6

Divide each side by '-3'.
m = -2

Simplifying
m = -2

See similar equations:

| 8+32-36-(-7)= | | f(x)=3x^2+4x-4 | | -64=-16x | | -x+13=x-13 | | 8+2(16-36)-(-7)= | | 6x/-2x/21=25/21 | | -5+-7-(-4)= | | 2+y=-7+2 | | x+4=105x-104 | | -4a=-28 | | u^2-12u+17=0 | | -5x+3(6x+-16)=191 | | -4y+42=-6+2y | | 0.4x-0.7+0.3x=7 | | 4(6.25)+3x=34.60 | | 6-5-3(2)=8 | | m^4+7m^2=0 | | 3u^2-48=0 | | y+10=20-y | | x+5/3= | | 2-h=-32 | | 10x^7/5x^2/7 | | f=-48n+22000 | | 5y-9=7+9y | | Y=-4.2+3.6X | | 15x+32=7x-28 | | 13-8x=-7-3x | | 2m-24=-34+7m | | 2x+4(3x+-7)=84 | | 4^3x^4/4x^2 | | .8x+8.6=4.2 | | 3/10z-3/4 |

Equations solver categories